A biodegradable silver oxide-treated hydroxyapatite nanoparticle (AgO@HA)-interlaced poly(etherimide)/poly(methylmethacrylate) membrane for blood purification: an in vitro study. Issue 11 (6th May 2022) - Sivasankari, Selvam; Kalaivizhi, Rajappan; Ganesh, Munuswamy Ramanujam; Anjum, Musthafa Shazia
Abstract : In this research article, we are reporting the AgO@HA-PEI/PMMA membrane, which is most promising when blood is exposed to membranes since they exhibit attractive biocompatible and biodegradable properties. Abstract : The growing prevalence of renal disorder and the scarcity of healthy kidneys for donation necessitate the research and development of new types of hemodialysis membrane. By incorporating silver oxide-doped hydroxyapatite (AgO@HA) nanoparticles (NPs) into polyetherimide (PEI)/polymethylmethacrylate (PMMA) mixed matrix membranes (MMMs), we would like to develop a hemodialysis membrane that is more productive and biocompatible. The effective incorporation of hydrophilic AgO@HA on PEI/PMMA membrane surfaces was confirmed through analyses of X-ray diffraction (XRD) and Fourier transform-infrared spectroscopy (FT-IR). The AgO@HA integrated PEI/PMMA matrix membrane enhanced the hydrophilicity, as evaluated by water contact angle (CA), water uptake ratio (WU), and swelling ratio (SR). AgO@HA had a greater bioavailability; hence these MMMs were considerably more biocompatible with blood and cells. They had a higher resistance to blood coagulation, hemodialysis assay and plasma recalcification time, and a longer clotting time. Then, the biocompatibility was analyzed by the cell viability and Acridine orange/ethidium bromide (AO/EtBr) technique. In addition, to determine the degradable percentage of the nanocomposite membrane, a biodegradability test was carried out using soil burial methods. All of these findings suggest that the AgO@HA-PEI/PMMA MMMs should be investigated further for use in blood-purifying applications.